Relationship of the complex regional pain syndrome after surgery in upper members - Souza, Tulio Alberto de Oliveira (2023)
The Complex Regional Pain Syndrome (SCDR) is a disease that affects the musculoskeletal system of the patient causing several signs of anatomical dysfunction. This syndrome can be triggered by surgical procedures, trauma, infections and musculoskeletal disorders. Its main feature is the change in the normal response to painful stimuli, becoming disproportionate to pain in the extremities and the triggering noxious event. To analyze possible correlations between the emergence of complex regional pain syndrome after performing surgeries in the upper limbs. This work aims to perform an integrative literature review based on the guiding question: is there a relationship between the onset of Complex Regional Pain Syndrome and surgery on the upper limbs? Then, a search for articles was carried out in the MEDLINE and LILACS databases, where 39 articles were found, using the following descriptors: “Complex regional pain syndrome”, “Postoperative period” and “Upper extremity”, duly registered in the Descriptors in Health Sciences. The Boolean operator AND was used in the search. The following inclusion criteria were used: texts available in full, in the languages: English and Portuguese, from the last ten years. Duplicate articles and those that did not focus on SCDR were excluded. At the end, 3 articles were selected to compose the study. Important information was obtained as a result, which points out that the appearance of SCDR after a surgical procedure is not rare, it can be observed that in carpal surgeries there is an involvement of 8.3% of patients with the syndrome. Thus, surgical treatment for the disease represents an index of 75%, providing improvements in the patient's well-being and quality of life. However, new therapies are employed, such as the use of Vitamin C during the postoperative period of shoulder surgeries as a prophylactic form for the development of SCDR. It is noteworthy that there is no scientific evidence to prove the association of SCDR with factors such as: age, BMI, smoking, gender, concomitant diseases and the profession of the individual who develops the disease. Thus, because most cases are associated with the involvement of injuries, SCDR has a high rate of occurrence due to performing orthopedic and soft tissue surgeries in the upper limbs. It is worth noting that further studies are needed on the subject discussed, given that there is a shortage in the national and international literature.